ASSESSMENT OF OPEN BURNING OF AGRICULTURAL WASTEIN BIU LOCAL GOVERNMENT AREA OF BORNO STATE, NIGERIA - FOLORUNSHO, JOSEPH OLANIYI (Advances in Social Sciences Research Journal, 2016)
Assessment of potential open burning of agricultural crop residue of post-harvest waste generations in Biu local government areas of Borno State, Nigeria was estimated. This is with a view of knowing the types, quantity and strength of these crop residues generated annually in the study area. The method adopted was field survey and focused group discussion of and the result collected. The total hectares of land cultivated for the major crop selected from the host communities were estimated to be 1450ha. in the year under study. From the study, maize, millet and rice are being produced in large quantity in the place visited. For maize alone in ten communities, 140 tonnes of waste is produced, 118 tonnes of sorghum, 115 tonnes of millet, 111 tonnes of rice and 53 tonnes of cowpea waste is produced. The major management measure adopted is burning which is not environmentally friendly. The annual quantity of agricultural crop residues generated for burning in these communities is estimated to be 381 tons. Among the entire communities selected, Maina Hari has the highest hectares of land cultivated during the period of field survey followed by Mangada and Mandafuma. The survey also revealed that farmers have difficulties in accessing information on environmental health hazard of open burning of agricultural waste. While some even lack any knowledge about health risk of burning crops residue, apart from increasing soil fertility to their farm and also facilitate land clearing prior to raining season. Regulatory efforts should focus on the identification and control of environmental airborne sources of pollution resulting from burning activities, which are currently the major origin of food chain contamination.